Paleoenvironmental control on trace fossils across a Mississippian carbonate ramp succession, Mobarak Formation, east of Central and Eastern Alborz, Iran. (May 2020) - Nasiri, Yaghub; Bayet-Goll, Aram; Mahboubi, Asadollah; Moussavi-Harami, Reza; Monaco, Paolo
Abstract: The Lower Carboniferous Mobarak Formation in the east of Central and Eastern Alborz Mountains, northern Iran, is deposited on a distally steepened carbonate ramp. Detailed facies analysis allowed to differentiate seven facies associations, includes deep marine basinal (FA1), toe-of-slope/outer ramp (FA2), ramp/slope (FA3), shallow open marine (FA4), bioclastic bars or shoal (FA5), lagoon (FA6) and intertidal flat (FA7). The trace-fossil suites of the studied successions are shown for the first time. Twenty eight ichnogenera were identified, i.e. Arenicolites, Asterosoma, Bergaueria, Chondrites, Cochlichnus, Diplocraterion, Halopoa, Helminthopsis, Helminthorhaphe ?, Helminthoidichnites, Gordia, Gyrochorte, Lockeia, Mammilichnis, Megagrapton, Nereites ?, Palaeophycus, Phycodes, Phycosiphon, Planolites, Protovirgularia, Rhizocorallium, Rosselia, Sinusichnus, Skolithos, Taenidium, Thalassinoides, and Zoophycos . The seven facies associations deposited in a wide range of physico-chemical conditions, show distinct proximal to distal trends. As a result of oxygen-depleted depositional conditions, only the tracemakers of Zoophycos survived in deep marine slopes, which were close to turbiditic sedimentation zones. The development of a benthic community under the stable condition and a long-term colonization window were documented by highly diverse suites of the Cruziana ichnofacies. Under a stressed environment (after tempestite deposition), the Skolithos ichnofacies displayed a low diversity of opportunistic ichnocommunity suite. The mixed Skolithos – Cruziana ichnofacies occur in the middle to distal lower inner ramp. The identification of the archetypal ichnofacies may document broad changes of environmental parameters such as variability in sedimentation rates, energy level, salinity, substrate properties/consistency, nature of nutrient supply and dissolved oxygen content. Relationships among different modes of ethology of tracemakers and sedimentary structures in the studied successions are used to clarify sedimentary conditions. Highlights: The Lower Carboniferous Mobarak Formation in the east Central and Eastern Alborz Mountains, is deposited on a distally steepened carbonate ramp. Detailed facies analysis allowed to differentiate seven facies associations, including FA1 to FA7. The trace-fossil suites of the studied successions are shown for the first time. The ichnofacies in the Mobarak Formation including.